The heterogeneous nuclear ribonucleoprotein K (hnRNPK) is a host factor required for dengue virus and Junin virus multiplication - Brunetti, Jesús Emanuel (2015)
Heterogeneous nuclear ribonucleoproteins (hnRNPs) are cellular factors involved in the replication of several viruses. In this study we analyzed the expression and intracellular localization of hnRNP A2 and hnRNP K in cell cultures infected with two viruses that cause human hemorrhagic fevers: dengue virus type 2 (DENV-2) and Junín virus (JUNV). We determined that DENV-2 promoted the cytoplasmic translocation of hnRNP K and to a lesser extent of hnRNP A2, meanwhile, JUNV infection induced an increase in hnRNP K cytoplasmic localization whereas hnRNP A2 remained mainly in the nucleus of infected cells. Both hnRNP K and hnRNP A2 were localized predominantly in the nucleus of JUNV persistently infected cells even after superinfection with JUNV indicating that persistent infection does not alter nucleo-cytoplasmic transport of these hnRNPs. Total levels of hnRNP K expression were unaffected by DENV-2 or JUNV infection. In addition we determined, using small interfering RNAs, that hnRNP K knockout inhibits DENV-2 and JUNV multiplication. Our results indicate that DENV-2 and JUNV induce hnRNPK cytoplasmic translocation to favor viral multiplication.